Miskonsepsi Materi Fungi (Jamur) pada Buku Biologi Kelas X SMA/MA - Nurhafizah Nasution; Aviva Tunasika Ginting; Izza Yani Umaroh; Bella Safitri; Reina Alpira Nashwa; Syarifah Widya Ulfa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
A variety of biology texbooks have been published in order to include regulatory demands and educational needs. So this research aims to identify misconceptions that exist in the material, fungi (fungi) in the revised 2013 curriculum class X Biology book, so that existing misconception are realized by teachers as educators, as well as the public in general. The type of research cerried out in this research is quantitative descriptive research in the form of identification, classification and descriptive analysis of misconceptions on material concepts, fungi (fungi) found in class X high school biology open books. This research was carried out from April to June 2024, book what is explained in this research is the biology high school book published by erlangga. The content of the material contained in the book being analyzed is appropriate because the book contains groupings of fungi based on reproductive characteristics and relatings them to everyday life. But there are still some misconceptions such as the difference between higher plants, and plants, levels low, fungal body shape, fungal classification, lichen reproduction and thallus morphologi in lichen.